Proceso de atención de enfermería en paciente de 35 años de edad con politraumatismo más amputación de miembro inferior izquierdo. - Flores Ordoñez, Cristhian Javier (2021)
Trauma is defined as a set of injuries caused by accidents in different ways that turn out to be gaps affecting the body, changing its lifestyle, environment and condition for the patient and their caregivers. The following work will present a clinical study on a 35-year-old patient with Diagnosis of Polytrauma with amputation of the lower left limb, fulfilling the objective of applying the nursing care process, for which care plans were developed following the steps for training. of estte. The patient was assessed through functional patterns identifying the potential problems that the patient presented, designating the Diangostic Nurses who were related to the patient's symptoms by planning the results, the activities that were applied during their hospitalization were established where we improved, their comfort, we morally support the patient and family members and together with the medical treatment the clinical condition of the patient was optimized. We conclude that our clinical study was based on the theoretical framework, basing what was shown in his clinical history, this was related to the symptoms and complications that I refer the patient. The application of the nursing process allowed the nurse to provide the care that the patient deserved.